Deep-Sea Carbonates Are a Reservoir of Fossil Microbes Previously Inhabiting Cold Seeps - Wang, Yong; Li, Wenli; Li, Qingmei; Zhou, Yingli; Gao, Zhaoming; Feng, Dong (Frontiers in Marine Science, 2021)
Carbonates are globally distributed particularly around deep-sea cold seeps. The embedded microbes are fossil records of the past bioprocess but metagenomes of the carbonates have not been fully studied. In this study, we report microbial community structures and genomes of dominant species in cold-seep carbonates from the South China Sea (SCS) and Gulf of Mexico (GoM). The carbonates contained both anaerobic microbes represented by methane oxidizing archaea (ANME) and aerobic ammonia-oxidizing archaea (AOA). The samples from GoM were mostly composed of small microbial groups, indicating heavy degradation of the fossil microbes. The composition of the carbonate communities differed from that of cold seep sediments, suggesting alteration of cold-seep microbial structures during formation and weathering of carbonates. Extraction of 18S rRNA genes from metagenomic reads revealed prevalence of fungal species in the carbonates of the GoM. Genome binning resulted in 10 genomes for dominant prokaryotic species. The ANME genomes showed a short genetic distance to the relatives from the current cold seep sediments; the AOA genomes were affiliated with alpha ecotype dominating deep-sea sediments. Our study reports the genomes in ancient carbonates and sheds lights on microbial role in formation and bioweathering of carbonates.